“A STUDY ON THE FACTORS INFLUENCING WORKPLACE WELLBEING, EMOTIONAL, PSYCHOLOGICAL, FINANCIAL, ENVIRONMENTAL, CAREER, AND OVERALL JOB SATISFACTION AMONG EMPLOYEES IN THE DIAMOND MANUFACTURING INDUSTRIES OF SURAT CITY” - Mr. Jvalant Panday and Dr.Neelima Kamjula (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This study aims to provide valuable insights into the factors affecting employee satisfaction in the diamond manufacturing industries of Surat City. By understanding these factors, organizations can develop targeted strategies to enhance workplace wellbeing, emotional and psychological health, financial stability, environmental conditions, and career growth opportunities. The findings will contribute to improving employee satisfaction and, ultimately, organizational performance in this vital sector.This study investigates factors influencing employee satisfaction in Surat City's diamond manufacturing industry through a descriptive research design, using primary data from questionnaires and secondary data from literature. A sample of 44 employees is analyzed using frequency analysis, descriptive statistics, and the Kruskal-Wallis test. The study's findings aim to provide actionable recommendations for enhancing employee wellbeing and organizational performance, though its small sample size and regional focus may limit generalizability.The study reveals significant gender disparities, departmental distributions, and job positions among 40 employees in Surat's diamond manufacturing industry. Key findings include high satisfaction with co-worker relationships and punctual salary payments, but low satisfaction with mental health support and financial benefits. The Kruskal-Wallis test highlights that shift schedules significantly impact feelings of respect, workplace relationships, job target achievability, and learning opportunities, emphasizing the need for tailored management strategies.